Straying Off Course: The Negative Impact of Mind Wandering on Fine Motor Movements. Issue 2 (7th February 2022) - Dias da Silva, Mariana Rachel; Postma, Marie
Abstract: The goal of this study was to examine how various degrees of perceptual decoupling during mind wandering affect fine motor control. We hypothesized that while under normal circumstances attention ensures an optimal control strategy that leads to accurate motor performance, during mind wandering the process becomes disrupted. In this study, we conducted a computer-based experiment with a tracking task. During mind wandering, motor movements were more erratic and less variable, indicative of reduced attentiveness to the continuous demands of the external task. Importantly, the deeper the reported mind wandering, the less accurate and less variable were the mouse movements, suggesting that perceptual decoupling may take place in a graded rather than in an all or nothing manner. Greater movement intermittency was associated with higher tracking accuracy, suggesting that more corrective movements toward a moving target were functional to task performance. Moreover, greater variance in velocity was negatively correlated with tracking accuracy. These findings suggest that periods of inattention to the task have a negative impact on fine motor movement control by making behavior unpredictable, providing support for the idea that there is a decoupling of sensory-motor processes during mind wandering.